Dietary- but not exercise-induced acute iso-energetic deficit result in short-term appetitive compensatory responses in adolescents with obesity. (1st February 2023) - Fillon, Alicia; Pélissier, Léna; Beaulieu, Kristine; Charlot, Keyne; Siroux, Julie; Bagot, Sarah; Bailly, Mélina; Boscaro, Audrey; Finlayson, Graham; Boirie, Yves; Duclos, Martine; Isacco, Laurie; et al.
Abstract: Background: Producing negative energy balance rests on the creation of energy deficits that have been shown, depending on their modality, to induce potential appetitive compensatory responses. The aim of this study was to compare energy intake (EI), appetite feelings, and the hedonic responses to equivalent acute energy deficits induced by exercise versus energy restriction in adolescents with obesity. Methods: In a within-participants design, seventeen adolescents with obesity (12–16 years, Tanner stage 3–5, 9 males) randomly completed three conditions: i) control (CON); ii) deficit induced by diet only (Def-EI); and iii) deficit induced by exercise only (Def-EX). Lunch was calibrated to generate a 400-kcal deficit in Def-EI and remained similar in CON and Def-EX. A 400-kcal deficit was created through a cycling bout set at 65% VO2peak in Def-EX. Ad libitum EI, macronutrient intake and relative EI (REI) were assessed at dinner, subjective appetite sensations taken at regular intervals, and food reward measured before dinner. Results: Food intake at dinner was greater in Def-EI (1112 ± 265 kcal) compared to CON (983 ± 277 kcal; p = 0.005) and Def-EX (1009 ± 281 kcal; p = 0.025). Absolute protein and lipid intake were significantly higher in Def-EI (52.4 ± 9.5 g and 36.8 ± 8.9 g respectively) compared with both CON (44.9 ± 12.6 g; p = 0.001 and 33.8 ± 10.1 g; p = 0.002 respectively) and Def-EX (47.3 ± 11.8 g, p = 0.018, 35.4 ± 10.1 g, p = 0.036 respectively). Area under the curve (AUC) for hunger, desire to eat and prospective food consumption were significantly higher in Def-EI compared with both CON (p = 0.0001) and Def-EX (p = 0.0001). AUC for fullness was significantly lower on Def-EI compared with CON and Def-EX (p = 0.0001). Implicit wanting for sweet food was significantly lower on Def-EX (p = 0.031), relative to CON. Conclusion: Appetitive compensatory responses that are observed after iso-caloric energy restriction in adolescents with obesity are absent with acute exercise, which could contribute to optimize our impact on short-term energy balance.